Traditional knowledge in an agroforestry system and perspectives about agroecological practices in Nahua communities (Agro Productividad, 2024)
ABSTRACTObjective: To identify traditional knowledge associated to the traditional agroforestry system (TAFS)integrated by corn-coffee-allspice and to recognize perceptions and interests of Nahua communities towardsthe incorporation of agroecological practices.Design/methodology/approach: Work was done in two Nahua communities of Cuetzalan, Puebla, Mexico,devoted to the production of corn (Zea mays L.), coffee (Coffea arabica L.) and allspice (Pimenta dioica Mill), inTAFS. A qualitative research approach was used, in which semi-structured interviews were conducted.Results: A representative population sample was interviewed; 74% of the population were women, 38% wasolder than 65, 100% self-described as Nahua and recounted that maintenance of the TAFS is a family activity.Performing soil and organic matter conservation was manifested by 29%; 26% described promoting the diversityof species (cultivated and tolerated); 9% described establishing Scaptotrigona mexicana (endemic pollinator) in theplot; 65% knows an agroecological practice, and of this portion, 42% would like to use organic fertilizers, 41%considers that management of fertility and soil conservation are key to maintain the TAFS.Limitations on study/implications: The findings reported are applicable to the context of Nahuacommunities in the Sierra Norte region of Puebla.Findings/conclusions: There are traditional understandings associated to the TAFS. These have an approachof adaptation and emulation of local environmental characteristics to satisfy self-consumption. The approachof integral management of the agroecosystem tends to sustainability. The perception of the incorporationof agroecological practices is positive, and there is special interest in the management of soil fertility andconservation.